The effect of n-butanol and 2-aminoethanol on the in vitro androgenesis of maize - Földesiné Füredi, Petra Katalin; Ambrus, Helga; Barnabás, Beáta (Acta Biologica Szegediensis, 2011)
Contrary to wheat, in our experiment in vitro androgenic induction of maize microspores was not substantially influenced by n-butanol and 2-aminoethanol treatments. Embryo production of the treated live microspores was increased by max. 7-8% after 6-hour treatment with 0.4% n-butanol and 4 mM 2-aminoethanol. The plant regeneration frequency of the long-term treated (18 hs. with 2mM 2-aminoethanol and 18 hs. with 0.2% n-butanol) microspores was almost 5 times higher that of control. Unlike behaviour of the microspores of this two cereal species could have derived from their altered cytoskeletal systems.